Molecular dynamics simulation of frictional properties of Couette flow with striped superhydrophobic surfaces under different loads. Issue 32 (2nd August 2019) - Hu, Chengzhi; Tang, Dawei; Lv, Jizu; Bai, Minli; Zhang, Xiaoliang
Abstract : There was a critical load ( P crit ), such that the friction-reduction of superhydrophobic surfaces appeared only when the load < P crit . Abstract : To reveal the effect of a striped superhydrophobic surface on frictional properties, molecular dynamics simulations were carried out to study the frictional properties of Couette flow. In particular, the influence of load on flow properties was considered in this work. The results showed that regions of gas in the groove and a low density region near the superhydrophobic surface were formed. Under a certain load, convex menisci appeared on top of the groove and some fluid atoms were trapped in it. Compared with the smooth hydrophobic surface, the striped superhydrophobic surface showed a reduction in friction owing to reduced liquid–solid contact area. With increasing load, the number of fluid atoms trapped in the groove increased prominently, which increased the friction force of the striped superhydrophobic surface more quickly. There was a critical load ( P crit ), such that the friction-reduction property of striped superhydrophobic surfaces appeared only when the load was smaller than it. By reducing the distance between adjacent stripes, the rate of increase in the number of fluid atoms trapped in grooves with load decreased significantly, which increased P crit . Under a large load, the friction force decreased with the distance between adjacent stripes. However, under a small load we observed the opposite trend.